Efficacy and safety of Yinchen Sini decoction in treating biliary atresia patients after Kasai portoenterostomy: A systematic review and meta-analysis protocol. Issue 2 (January 2019) - Chen, Guoming; Huang, Chuyao; Lu, Jiaxin; Huang, Ruilan; Zhang, Jie; Chen, Ziyin; Xu, Hua
Abstract: Background: Biliary atresia (BA) is a neonatal obstructive biliary tract disease in which the intrahepatic and extrahepatic bile ducts are obstructed and can lead to congenital biliary atresia of cholestatic cirrhosis and eventually liver failure. It has been confirmed that the Kasai portoenterostomy is an effective treatment for BA. But most patients still face complications, such as cholangitis and liver fibrosis. Yinchen Sini decoction (YCSND), a traditional herbal formula, is used as a treatment for BA after Kasai portoenterostomy. And it is supported that YCSND can improve jaundice and liver fibrosis through multiple targets and pathways. Based on the published literature, this study aims to evaluate the current situation in the treatment of BA in children with YCSND. Methods: The following databases will be searched until October 2018: PubMed, The Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese biomedical literature database (CBM), Wan Fang Database, Chinese Scientific Journals Database (VIP) and other sources such as Hand searching, Conference proceeding, International Clinical Trials Registry Platform and Chinese Clinical Trials Registry. All randomized controlled trials (RCTs) of YCSND or related formula as a treatment for postoperative patients of Kasai portoenterostomy for BA will be collected. Data extraction and risk of bias assessments will be carried out by 2 verifiers independently. The risk of bias will be evaluated through the Cochrane risk of bias tool. Review Manager software (RevMan V.5.3.0) and STATA 15 will be used for statistical analyses. Results: This study will provide a high-quality synthesis of current evidence of YCSND in treating children undergoing Kasai portoenterostomy for BA from several aspects. Conclusion: The conclusion of the meta-analysis will offer evidence for deciding whether YCSND is an effective measure for children undergoing Kasai portoenterostomy for BA. Ethics and dissemination: Not only will this systematic review be published in a peer-reviewed journal, but it will also be propagated electronically and in print. The review will bring patients benefit and provide practitioners reference in the fields of conventional medicine. PROSPERO registration number: PROSPERO CRD 42018111321.